The Fight against Marriages of Convenience in the EU and in Hungary - Töttős, Ágnes (Pécs journal of international and European law, 2015)
The aim of this study is to reveal the tendencies of the most typical form of abuse linked to free movement of EU citizens and their family members, namely marriages of convenience, through the lenses of Hungarian practice. Hoping that knowing more about these tendencies and getting more prepared for fighting against such abuses can help to achieve even more complete free movement, the tools of this fight, especially the most recent Handbook of the EU are introduced and analysed in the study.